Malaysian child infected with Plasmodium vivax via blood transfusion: a case report - Anthony, C.N.; Lau, Y.L.; Sum, J.S.; Fong, M.Y.; Ariffin, H.; Zaw, W.L.; Jeyajothi, I.; Mahmud, R. (2013)
Malaria may be a serious complication of blood transfusion due to the asymptomatic persistence of parasites in some donors. This case report highlights the transfusion-transmitted malaria of Plasmodium vivax in a child diagnosed with germ cell tumour. This child had received blood transfusion from three donors and a week later started developing malaria like symptoms. Nested PCR and sequencing confirmed that one of the three donors was infected with P. vivax and this was transmitted to the 12-year-old child. To the best of the authors' knowledge, this is the first reported transfusion-transmitted malaria case in Malaysia.